2019
DOI: 10.1111/hsc.12854
|View full text |Cite
|
Sign up to set email alerts
|

Health, well‐being, and social support in older Australian lesbian and gay care‐givers

Abstract: Informal care‐givers play an important role in society, and many of the people who provide this care are lesbian women and gay men. Being a care‐giver is known to be associated with poorer health and well‐being, and lesbian and gay care‐givers report experiences of stigma and discrimination in the care‐giving context. This study involved a survey of 230 lesbian women and 503 gay men aged 60 years and over living in Australia, of which 218 were care‐givers. We compared care‐givers to non‐caregivers on a range o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 50 publications
(137 reference statements)
0
18
0
Order By: Relevance
“…Previous research in Australia on concerns about accessing ageing and health care services has found that lesbian women were more concerned about services not recognising same‐sex relationships than were gay men (Hughes, 2009). Studies have further found that women in general tend to access health services more often than men (Mukhtar et al., 2018) and research in Australia shows that older lesbian women are more likely to be caregivers than older gay men (Alba et al, 2020), all of which may result in additional contact with services. It is therefore possible that some gender differences were related to women having greater experience of services and therefore being more aware of challenges posed by issues related to inclusiveness, as well as greater awareness of what services are available.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research in Australia on concerns about accessing ageing and health care services has found that lesbian women were more concerned about services not recognising same‐sex relationships than were gay men (Hughes, 2009). Studies have further found that women in general tend to access health services more often than men (Mukhtar et al., 2018) and research in Australia shows that older lesbian women are more likely to be caregivers than older gay men (Alba et al, 2020), all of which may result in additional contact with services. It is therefore possible that some gender differences were related to women having greater experience of services and therefore being more aware of challenges posed by issues related to inclusiveness, as well as greater awareness of what services are available.…”
Section: Discussionmentioning
confidence: 99%
“…Sample items are: 'When I need suggestions on how to deal with a personal problem, I know someone I can turn to' and 'I don't often get invited to do things with others'. In an Australian study of gay and lesbian people (Alba et al, 2020), scale score reliability was excellent (α = 0.90). Possible scores ranged from 12 to 48.…”
Section: Social Supportmentioning
confidence: 99%
“…For example, Grigorovich [ 35 , 36 ] explores quality of care related to service provider knowledge of, and comfort with, sexual diversity and the decision-making processes related to disclosure of older lesbian and bisexual women during interactions with home care service providers, citing experiences of overt and subtle heterosexism and discrimination. References to home care in 2SLGBTQ+ health-related literature have often been anecdotal and/or represent the perspectives and insights of service providers rather than sexual and gender minority people themselves [ 31 , 38 , 39 , 40 , 41 , 42 ].…”
Section: Introductionmentioning
confidence: 99%